THE RELATIONSHIP OF THE QUALITY OF NURSING SERVICES WITH LEVEL OF SATISFACTION OF INPATIENT PATIENTS AT SILOAM HOSPITAL MANADO - Lontoh, Ester; Manengkey, Olvin Kristin; Nindi, Engryne; Maengga, Santiani (HEARTY, 2024)
The quality of nursing services is main and contributes to health recovery, community welfare, and maintaining hospital stability. Patient satisfaction is a purpose for determining how efficiently healthcare is presented. The aim of this study is to conduct research on the correlation between the quality of nursing services and the satisfaction level of inpatients in Siloam Hospital Manado. The method used was a cross sectional study with a population of 166 patients. The number of samples was 62 respondents after being selected using stratified random sampling techniques. The data analysis was use univariate and bivariate (chi-square using fisher exact test analysis) technique to know related among variables. The result of the study showed the information about nursing service quality is significantly related to the level of satisfaction of inpatient patients. Therefore, the results of this research fully support every hospital in Indonesia to maintain nursing services quality in each institution.